Design aspects of post-war reconstruction and renovation of public urban spaces - Demessie, Mekuria Kelkay; Yakovets, Inna (Art and Design, 2025)
This study aimed to systematise existing approaches, principles, and trends related to the restoration and renovation of public spaces, while also identifying the actual needs of residents through surveys. Based on the findings, recommendations are proposed for the post-war development of public urban spaces. The primary methods used for data collection included visual analysis, individual surveys, and interviews with residents to determine their genuine needs. The results were structured using general scientific research methods. The survey revealed that 63% of respondents expressed a willingness to participate in the renovation and revival of damaged public urban spaces. 43% believed the restoration process should retain historical elements that existed prior to destruction, supplemented with new components. Among those surveyed, 31% preferred complete restoration to the pre-war state without alterations, while 36% wished to see elements of military memorial themes incorporated into the renewed public spaces. The study outlined key aspects highlighting the significance of public space in the functioning of a modern city and identifies major challenges associated with their post-war formation. Methodological recommendations have been provided to guide the formation, restoration, and renovation of public spaces, taking into account both residents’ interests and current trends. Existing approaches, ideas, and proposals for the renewal and renovation of public urban spaces have been systematised and supplemented with new concepts. Evaluation criteria for public urban spaces have been refined based on indicators such as functional and spatial organisation, principles of public space formation, development prospects, and public participation. Mechanisms for civic engagement in the restoration and renovation of public spaces have been proposed for all stages – discussion, design, planning, and practical implementation. The findings of this study may be applied by designers and architects in developing projects for the reconstruction of war-damaged public spaces, as well as by local authorities during their implementation.